Corrosion behavior of iron plates in cementitious solution at 80 °C in anaerobic conditions. (1st July 2020) - Pally, David; Le Bescop, Patrick; Schlegel, Michel L.; Miserque, Frédéric; Chomat, Laure; Neff, Delphine; L'Hostis, Valérie
Highlights: Iron was corroded at 80 °C in anoxic cement-containing conditions. Corrosion damage is limited to <1.5 μm after 160 days. A corrosion duplex layer dominated by Fe(III)-containing hydroandratite formed. A thin Fe(III)-rich film in contact with iron likely passivated metal. A corrosion mechanism explaining observations is proposed. Abstract: Iron was corroded in anoxic cementitious (pH 13.2) media (filtered porewater or cement slurry) at 80 °C; corrosion products were investigated by microscopic techniques. A thin film of magnetite (Fe3 O4 ) formed during the first immersion days. For longer immersion times (90 days) in cement slurry, hydroandradite (HA) (Ca3 (Fe 3+ )2 (SiO4 )y (OH)4(3-y) ) formed a dense outer layer and an heterogeneous inner layer. A thin oxide layer is always observed in contact with metal and is believed to correspond to a protective barrier. Our results suggest that in the conditions of the Belgian supercontainer for radioactive waste disposal, a passive layer can form slowing down corrosion.